(untitled) (Journal of the College of Basic Education, 2026)
This study has conducted to investigate Iraqi EFL students’ perceptions on the relationship between artificial intelligence technology and improving academic performance in Al-Mustansaryia University. The researcher utilized Descriptive Corelational Quantitative. The researcher prepared a closed-ended questionnaire for the purpose of collecting and analyzing data according to the frequency and repetition of the participants’ answers. 150 English language Iraqi students from different parts of Iraq. This finding highlights the importance of AI in improving academic performance and suggests that incorporating AI technologies into educational settings can positively impact on students’ learning outcomes. While there seems to be a high correlation between AI and academic performance, other factors might possibly be at play. To determine and comprehend the mechanisms via which AI improves performance, more investigation and analysis would be required.